Mediating effects of patient safety perception and willingness to participate in patient safety on the relationship between health literacy and patient participation behavior among inpatients - Won, Mi Hwa; Shin, Sun-Hwa (Frontiers in Public Health, 2024)
Introduction In recent years, patient safety activities have shifted from being centered on healthcare providers to involving patients themselves. Health literacy of inpatients has a direct impact on patient participation behavior. Patient safety perception was also associated with willingness to participate in patient safety and patient participation behavior. Therefore, this study aimed to investigate the mediating effects of patient safety perception and willingness to participate in patient safety on the relationship between health literacy and patient participation behavior among inpatients. Methods This cross-sectional study was conducted to confirm the relationship between study variables. A total of 262 inpatients were recruited from patients admitted to the ward of a tertiary general hospital between October and November 2023. Participants were invited to complete self-reported questionnaires that measured health literacy, patient safety perception, willingness to participate in patient safety, patient participation behavior, and demographic information. Data were analyzed using a dual mediation model applying the PROCESS macro (Model 6) with 95% bias-corrected bootstrap confidence intervals. Results This study analyzed the direct effects of health literacy on patient safety perceptions and patient participation behavior. Health literacy indirectly affected patient participation behavior through patient safety perceptions and willingness to participate in patient safety. Regarding the relationship between health literacy and patient participation behavior, patient safety perceptions and willingness to participate in patient safety showed a significant dual mediating effect. Conclusions This study identified the factors that promote patient participation behavior among inpatients. The mediating effect of patient safety perception on the relationship between health literacy and patient participation behavior was found to be strong. Building health literacy among inpatients ensures patient safety by increasing patient safety perceptions.